Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

$$\begin{align*} x + 2y - z &= -3\\ 2x - 4y + z &= -7\\ -2x + 2y - 3z &= 4 \end{align*}$$

I multiply (1) by $-2$ and get $-2x-4y+2z=6$ and then add it to (2) which gives me $-8y+3z = -1$.

I add (2) and (3) and get $-2y-2z=-3$

I take the first result and get $$y=\frac{-1-3z}{8}$$ putting that into $-2y-2z=-3$ I get $$\frac{-2(-1-3z)}{8-2z}=-3$$ which gives me $2+6z-16z = -24$, which gives me $10z=-26$ which I know isn't right already. I messed up the math somewhere, but I have done this problem about a dozen times and always get the wrong answer no matter what.

share|improve this question
    
I have done this so many times, how did you come up with that? I just can't get it, I am getting confused on what to do with a negative times a series of number divided by a number. –  Adam Apr 17 '11 at 19:27
1  
From $-8y+3y=-1$ you get first $-8y=-1-3y$. Then $y=\frac{-1-3y}{-8}=\frac{1+3y}{8}$, not $y=\frac{-1-3y}{8}$, because you have to divide $-8y=-1-3y$ by $-8$ and not by $8$. –  Américo Tavares Apr 17 '11 at 19:33

2 Answers 2

up vote 3 down vote accepted

You should get $y=\frac{1+3z}{8}$, not $y=\frac{-1-3z}{8}$.

The answer should be x=-3, y=1/2, z=1.

share|improve this answer
    
I just messed up basic math again, this is why I fail all my tests, I took my time, double checked everything, attempted to prove my order of operations was correct by making up a nother series of numbers and multiplying it both ways to see which gave me the proper asnwer, then using that on my equation. –  Adam Apr 17 '11 at 19:39

Your mistake is when you solve for $y$ from the new (2). You have $$-8y + 3z = -1$$ from which you get $$-8y = -1 -3z.$$ If you now divide by $-8$, you get $$y = \frac{-1-3z}{-8} = \frac{-(1+3z)}{-8} = \frac{1+3z}{8}.$$

I should also point out that you need to be careful with the order. After you add a multiple of the first equation to the second, your system now looks like $$\begin{align*} x + 2y - z &= -3\\ - 8y + 3z &= -1\\ -2x + 2y - 3z &= 4 \end{align*}$$ so you are not adding the second equation to the third to eliminate $-2x$. Rather, you first add equation (2) to equation (3), and then you add -2 times the first equation to the second.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.